2007
DOI: 10.1158/1055-9965.epi-07-0160
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variant of Manganese Superoxide Dismutase (SOD2 V16A) Polymorphism Is Associated with Prostate Cancer Risk in the Prostate, Lung, Colorectal, and Ovarian Cancer Study

Abstract: Superoxide dismutase (SOD) plays a key role in the detoxification of superoxide free radicals. We evaluated the association of prostate cancer with genetic polymorphisms in SOD1 (CuZn-SOD; IVS3-251A>G), SOD2 [MnSOD; Ex2+24T>C (V16A)], and SOD3 (EC-SOD; IVS1+186C>T, Ex3-631C>G, Ex3-516C>T, and Ex3-489C>T), the three main isoforms of SOD. Prostate cancer cases (n = 1,320) from the screening arm of the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial were frequency matched to nondiseased controls (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
89
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 30 publications
13
89
1
2
Order By: Relevance
“…The frequency distributions of C and T alleles were found to be respec- has the similar CC genotype frequency as seen in AfricanAmerican [35], Finn [36], and Italian populations [37]. We detected considerably lower CC genotype frequency than those found in Korean [38], Japan [39], Chinese [40] and Taiwan [41] populations and higher frequencies than those found in American [23], Polish [42], Danish [43], German [44] and Russian [45] populations. Eventually, CC genotype frequency in populations of the eastern countries, were lower (between 0-17%) found than the western countries (between 42-67%) ( Table 4).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The frequency distributions of C and T alleles were found to be respec- has the similar CC genotype frequency as seen in AfricanAmerican [35], Finn [36], and Italian populations [37]. We detected considerably lower CC genotype frequency than those found in Korean [38], Japan [39], Chinese [40] and Taiwan [41] populations and higher frequencies than those found in American [23], Polish [42], Danish [43], German [44] and Russian [45] populations. Eventually, CC genotype frequency in populations of the eastern countries, were lower (between 0-17%) found than the western countries (between 42-67%) ( Table 4).…”
Section: Resultssupporting
confidence: 75%
“…SOD2 is a mitochondrial enzyme that catalyzes the formation of H 2 O 2 from superoxide radicals. The variant allele of SOD2 has been associated with elevated risk of breast [22], prostate [23], lung [24] and ovarian [25] cancers and non-Hodgkin's lymphoma [26].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, of the 22 studies (Wang et al, 2001;Woodson et al, 2001;Lin et al, 2003;Liu et al, 2004;Wang et al, 2004;Li et al, 2005;Taufer et al, 2005;Ho et al, 2006;Choi et al, 2007;di Martino et al, 2007;Ergen et al, 2007;Kang et al, 2007;Arsova-Sarafinovska et al, 2008;Iguchi et al, 2008;Mikhak et al, 2008;Bica et al, 2009;Cheng et al, 2009;Iguchi et al, 2009;Sun et al, 2009;Zejnilovic etal., 2009), the sample size ranged between 100 and 3,030, and there were twelve studies on prostate cancer, four studies on esophageal cancer, and six studies on lung cancer. All studies, except for five of them (Taufer et al, 2005;Bica et al, 2009;Sun et al, 2009;Zejnilovic et al, 2009), indicated that the distribution of genotypes in the controls was consistent with HardyWeinberg equilibrium, while only one study conducted by Lin et al (2003) contained no data for Hardy-Weinberg equilibrium.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Associations between six single-nucleotide polymorphisms (SNPs) of the earlier-mentioned five genes and CRC have been reported in different ethnic groups (Smith et al, 2001;Landi et al, 2003Landi et al, , 2005Krzesniak et al, 2004;Jiang et al, 2005;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Berndt et al, 2006;Huang et al, 2006;Koh et al, 2006;Kuriki et al, 2006;Matsuo et al, 2006;Moreno et al, 2006;Theodoropoulos et al, 2006;Tranah et al, 2006;Hansen et al, 2007;Kang et al, 2007;Stern et al, 2007;Vogel et al, 2007;Yin et al, 2007;Kury et al, 2008;Funke et al, 2009;Khatami et al, 2009;Tsilidis et al, 2009;Yang et al, 2009;Engin et al, 2010;Meplan et al, 2010;Loh et al, 2011;Wu et al, 2011;Crous-Bou et al, 2012;Gil et al, 2012). These six variants comprised rs12917 and rs2308321 of MGMT, rs1229984 of ADH1B, rs4880 of SOD2, rs2228001 of XPC, and rs1801282 of PPARG.…”
Section: Introductionmentioning
confidence: 99%